Revisiting the Issue of the Place of Economic Experiment in the Study of the Economic Dynamics Cyclicity - SIMCHENKO, Nataliia; TSOHLA, Svetlana (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
On the basis of theoretical and methodological studies of the economic cycle theories, the paper represents the results of the evolutionary development of this area of science. The authors formulate a hypothesis regarding the effect of the implementation of economic experiments at the macro level on the cyclical nature of economic development. The critical analysis of the evolution of the basic theories and concepts of economic cycles was made. The essential role of the concept of ‘economic experiment’ was studied in relation to the cycle theory. Classification criteria of typology of economic experiments were identified. Based on the analysis of the successful implementation of a number of large-scale economic experiments, the authors make conclusion that regardless of the causes of the cycles, a prerequisite for system transformations at the national level are the economic crisis. The efficiency of the implementation of macro-experiments depends on the level of development of institutional environment and, above all, on the basic economic institutions.
Keywords: Cycle Theory; economic dynamics; economic experiment